Four-dimensional light shaping: manipulating ultrafast spatiotemporal foci in space and time - Sun, Bangshan; Salter, Patrick; Roider, Clemens; Jesacher, Alexander; Strauß, Johannes; Heberle, Johannes; Schmidt, Michael; Booth, Martin J. (Light: Science & Applications, 2018)
The spectral dispersion of ultrashort pulses allows the simultaneous focusing of light in both space and time, which creates so-called spatiotemporal foci. Such space–time coupling may be combined with the existing holographic techniques to give a further dimension of control when generating focal light fields. In the present study, it is shown that a phase-only hologram placed in the pupil plane of an objective and illuminated by a spatially chirped ultrashort pulse can be used to generate three-dimensional arrays of spatio-temporally focused spots. By exploiting the pulse front tilt generated at focus when applying simultaneous spatial and temporal focusing (SSTF), it is possible to overlap neighboring foci in time to create a smooth intensity distribution. The resulting light field displays a high level of axial confinement, with experimental demonstrations given through two-photon microscopy and the non-linear laser fabrication of glass.
Keywords: Micro-optics; Nonlinear optics; Ultrafast photonics